Effect of Fermentation Conditions and Plucking Standards of Tea Leaves on the Chemical Components and Sensory Quality of Fermented Juice - Ping Tang; Dan-Yu Shen; Yong-Quan Xu; Xing-Cai Zhang; John Shi; Jun-Feng Yin (Journal of Chemistry)
The effects of fermentation conditions (temperature, time, and pH) and plucking standards (one leaf and a bud to four leaves and a bud) on the chemical components and sensory quality of the fermented juices processed from crushed fresh tea leaves were investigated. The results showed that optimum fermentation conditions that resulted in fermented juices of the best sensory quality and the highest content of TFs were a temperature of 35°C, time duration of 75 min, and pH 5.1. The fermented juices processed from new shoots with three leaves and a bud or four leaves and a bud afforded high overall acceptability and TF concentration. These differences arise because tea leaves with different plucking standards have different catechin content and enzyme activities. Fermented tea juice possessed higher concentrations of chemical components such as soluble solids, amino acids, and TFs and exhibited better sensory quality as compared to black tea infusion. The TF concentrations decreased as the pH of the fermenting juice increased, and the fermented juice showed the best overall acceptability. These results provide essential information for the improvement of the processing of black tea beverage by suggesting fermentation of fresh tea leaves as a better alternative to their infusion.